Effects of the COVID-19 Pandemic on Outpatient Providers in the United States - Chatterji, Pinka; Li, Yue (Medical care, 2021)
During the COVID-19 pandemic, there is concern that social distancing, fear of contagion, quarantining of providers, cancellation of elective procedures, media coverage about the pandemic, and other factors drastically reduced physician visits, putting severe financial strain on outpatient providers, and having unknown ramifications for health outcomes. We estimate the effect of the pandemic on utilization of outpatient services. Using 2010-2020 data from a national dataset, the Outpatient Influenza-like Illness Surveillance Network, we estimate the difference in outpatient care utilization during the time period of the COVID-19 pandemic versus the same weeks in prior years. Our findings indicate that the pandemic started to reduce visits during the week of March 15-21. The effect on visits grew until reaching a peak during the week of April 5-11, 2020, when the pandemic reduced the total number of outpatient visits per provider by 70% relative to the same week in prior years. We find negative effects of the pandemic on visits for non-flu symptoms as well as on visits for flu symptoms, but the magnitudes of these latter effects tended to be larger in magnitude. The pandemic's impact declined over time, and by the week of June 28 to July 4, 2020, there was no longer any difference in total visits per provider relative to the same week in prior years. Despite the resurgence of COVID-19 in June and July, we still find no effects on total visits when our data end in July 26 to August 1, 2020. Our findings show that one by-product of the COVID-19 pandemic in the United States is a large decline in the use of outpatient care which peaked around the week of April 5-11. Total outpatient visits rebounded completely and remain stable as of July 26 to August 1, 2020.